An observational study on musculoskeletal manifestations in type 2 Diabetes mellitus in rural population of Himachal Pradesh, India - Bhat, Towseef Ahmad; Jalalie, Ummer; Kashyap, Sanjay (International Journal of Research in Medical Sciences, 2019)
Background: The prevalence of diabetes mellitus (DM) is increasing at an alarming rate throughout world. Diabetes is mostly known for vascular and neurological complications. Musculoskeletal manifestations though not as serious as neurovascular complications can be very disabling. These may involve, the upper as well as the lower limb. This study was performed with am to find out the prevalence of musculoskeletal manifestations in type 2 diabetics in a far-flung district of Himachal Pradesh, India. Methods: Total 350 patients with type 2 DM were included in the study. All patients underwent screening for any musculoskeletal abnormalities. The patients with musculoskeletal abnormalities were further assessed to find the exact diagnosis according to predefined criteria. Results: The shoulder was the most commonly involved joint 21.7% of the patients followed by hand in 16.28% patients and knee in 13.18% patients. Foot was involved in 12% and hand in 7% of the patients. The commonest manifestation in upper limb was adhesive capsulitis in 19.1% and in lower limb was symptomatic knee osteoarthritis in 14.57% patients. Conclusions: Author observed high prevalence of musculoskeletal complications in type 2 diabetics in this study.